Effect of soybean cultivars sowing dates on seed yield and its correlation with yield parameters - Magdalena Borowska; Janusz Prusiński (Plant, Soil and Environment, 2021)
The article presents the effect of three sowing dates on the growth, development and yielding of four soybean cultivars of different earliness and under different temperature and precipitation conditions across the years. The seed yield from early sowing significantly correlated with the total precipitation in June and July, and at later dates, also with the total precipitation in August. The significantly highest soybean yields were collected from the sowing at a turn of April and May, and the highest seed and protein yield, as well as protein content in seed, were recorded for the mid-early Merlin cultivar. Neither the number and the seed weight per pod nor the 1 000-seed weight significantly depended on the sowing date. Over years, a significant, almost linear decrease in the plant height and the first pod setting height, the weight of nodules, the protein yield and the LAI (leaf area index) value was observed. High significant correlations were found between the seed yield and the plant height and the first pod setting height, as well as between the seed number and the seed weight per pod and the 1 000-seed weight as well as between the plant height and the first pod setting height.